Auctioning resource rights - Kenneth Hendricks; Robert H. Porter (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2013)
We review the issues involved in designing a mechanism for allocating resource rights. We focus on the case of exploration and development rights for oil and gas leases in U.S. federal lands to highlight the tradeoffs at play. The main issues concern the design of the lease contract, the design of the auction, and the supply of leases. A distinguishing feature of oil and gas leases is that the mechanism must not only solve the adverse selection problem of selecting the bidder with the highest valuation but also the moral hazard problem of ensuring that right holders make efficient investment decisions.
Keywords: 330; auctions; leases; oil and gas; royalty